Von den “Luftgebäuden” der Philosophie in der Stadt der Sprache: An Analysis of the Metaphors in the First Part of Wittgenstein’s Philosophical Investigations - Porcaro, Ciro (2023)
The present study has as its object three of the most frequent and representative metaphors of the first part (paragraphs from 1 to 133) of Ludwig Wittgenstein’s Philosophical Investigations. In particular, the analysis focuses on the following mappings: LINGUISTIC EXPRESSIONS ARE TOOLS, LANGUAGE IS A CITY and MEANING IS A PURE CRYSTAL. The methodological approach adopted in the study as well as the analytical proceedings are both borrowed from the theory of conceptual metaphor (see: Lakoff and Johnson 1980, Lakoff 1993 and Kövecses 2002, 2020). The three metaphors were identified through a careful manual search of the text. An automatic search for source domain vocabulary followed to identify any further instances of the metaphors. In a second step, the conceptual structure of the metaphors was outlined; the entailments of the mappings were listed and interpreted on the backdrop of the arguments developed in Wittgenstein’s work. Finally, a comparison of the structures of the three conceptual metaphors was made. The analysis revealed the existence of complex and coherent conceptual mappings motivating the use of the identified metaphorical expressions. The comparison among the three metaphors confirmed the hypothesis that the entailments of the first two mappings mentioned above are all consistent with each other, playing a fundamental role in the comprehension of Wittgenstein’s position on language and meaning. Conversely, the internal logic of the third metaphor reflects a conception of language rejected by the philosopher.
Keywords: Metaphor Analysis; Philosophical Investigations; German Linguistics; Philosophy of Language